O pensamento educacional de Francisco Lucrécio e Ironides Rodrigues - Santos, Gilca Ribeiro (2013)
Between the late 19th century and the first decades of the 20th century, under the influence of the positivist ideas, Brazil was facing an accelerated process of urbanization and industrialization. In educational field, the city was a place to the expansion of the school system, which was formed by different types of schools: public, private, laical, religious, technical, of homemaking. It was in this context that emerged several schools for specific groups, among which those intended for the \"people of color\". Two educational experiences organized by the Brazilian Black Front-BBF and Black s Experimental Theater- BET figure as successful experiences between the years 1930-1960. This research examines the educational thought of the Professor from the Literacy Course of the Black Front, Francisco Lucrécio and Professor of the Literacy Course of Black s Experimental Theater, Ironides Rodrigues who dedicated their lives to education and issues related to the black population.